Adaptations and reactions of the library sector to the crisis of public funding of culture - Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2013)
We describe how public funding for cultural and library services in Spain decreased in 2012. Therefore, we analyze the impact of this problem on library services, and explain some ways to reduce the damage, such as user contributions and crowdfunding (i.e., social microfinancing). We conclude by arguing that in any case public funding remains essential for stability of these services, and that library associations and librarians must demand it.
Keywords: Public libraries; Spain; Economic crisis; Budget; Impact; Financing; Crowdfunding.